TOWARDS A FIFTH ONTOLOGY FOR THE ANTHROPOCENE. Issue 4 (3rd July 2020) - Hamilton, Clive
Abstract: This paper argues that the conditions of the Anthropocene render the four ontologies described by Philippe Descola obsolete, and begins the search for a fifth ontology that speaks to the meaning of the arrival of the new epoch. The radically new dispensation destabilises all prior understandings of the human, of nature and of the relationship between the two. Before progress is possible, the Anthropocene must be correctly understood. The concept emerged in the year 2000 not as another term to describe the extent of human impact across the landscape, the environment or ecosystems, but as a new idea to capture a very recent change in the nature of human impact on the Earth as a total entity, activity of a kind and on a scale sufficient to shift the geological evolution of the planet itself. The emergence of humans as a force of nature represents a rupture in human history and in Earth history, and a shift in the ontological status of both humankind and the Earth. All previous ontological systems are Holocene ones. The Earth can no longer be characterised, as it has been in environmental philosophy and post-humanism, as passive and fragile, as our victim; it is increasingly marked by angry, violent and uncontrollable behaviour, all of which destroys the conceit of human mastery. However, this emphatically does not mean that humans are powerless and that our agency can be reduced to the "agencies" of other creatures. A new ontology must grasp the primal Anthropocene fact that humankind is so powerful and so exceptional that it can knowingly change the geological trajectory of the Earth. The essence of the Anthropocene is not technological but lies in the fact that technological humans have shifted the Earth into a "no analogue state." A fifth ontology might begin from the reconfiguration of time implied when humans became a geological force, and as a result the novel way we must look into the future and reconsider the nature of the being of humans. If an ontology is the expression of the emotional orientation of the times, then the grounds of a fifth ontology can be found in the "attunement" of the millions of striking school students. The essential disposition appears to be that of dread.